Wet Foams Stabilized to Self-Setting Porous Ceramics - Gyu Park, Jung; Pokhrel, Ashish; Basnet, Bijay; Zhao, Wei; Jin Kim, Ik (Asian Journal of Chemistry, 2013)
This study presents a novel method to produce self-setting inorganic foams with unique setting time and pore structure. The combination of the particle-stabilized foams with Portland cement reaction leads to a macro porous ceramic material which can be shaped and consolidated at room temperature. The foam microstructure and porosity can be tailored varying different parameters like setting temperature, humidity, cement and setting accelerator concentration. The final microstructure featured a porosity of nearly 65 % and a unique pore structure with prevailing hydration reaction of cement. As a result, self-setting ceramic composites with porosities ranging from 40 to 65 % and pores with sizes between 100 μm to 1 mm were achieved.